2016
DOI: 10.1002/aur.1593
|View full text |Cite
|
Sign up to set email alerts
|

Atypical sensory reactivity influences auditory attentional control in adults with autism spectrum disorders

Abstract: Frequent observations of atypical sensory reactivity in people with autism spectrum disorders (ASD) suggest that the perceptual experience of those on the Spectrum is dissimilar to neurotypicals. Moreover, variable attention abilities in people with ASD, ranging from good control to periods of high distractibility, may be related to atypical sensory reactivity. This study used auditory event-related potential (ERP) measures to evaluate top-down and bottom-up attentional processes as a function of perceptual lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 92 publications
2
19
3
1
Order By: Relevance
“…Multiple psychological and neurophysiological studies suggests that increased bottom-up and reduced [ 59 , 60 ], or optional, top-down processing may characterize AS [ 12 , 61 ], and determine some aspects of the AS cognitive profile. An increased feedforward flow of information from visual areas has not only been reported in autistic visual [ 59 , 60 , 62 , 63 ] but also somatosensory [ 64 ] and auditory [ 65 ] processing. Previous studies also reported that the enhanced perceptual abilities in AS [ 12 ] and the atypical importance of complex visual perception in autistic intelligence [ 10 ] may be, at least partially, supported by higher feedforward connectivity from visual areas.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple psychological and neurophysiological studies suggests that increased bottom-up and reduced [ 59 , 60 ], or optional, top-down processing may characterize AS [ 12 , 61 ], and determine some aspects of the AS cognitive profile. An increased feedforward flow of information from visual areas has not only been reported in autistic visual [ 59 , 60 , 62 , 63 ] but also somatosensory [ 64 ] and auditory [ 65 ] processing. Previous studies also reported that the enhanced perceptual abilities in AS [ 12 ] and the atypical importance of complex visual perception in autistic intelligence [ 10 ] may be, at least partially, supported by higher feedforward connectivity from visual areas.…”
Section: Methodsmentioning
confidence: 99%
“…The empirical literature search resulted in 4769 citations. After title and abstract screening was completed, 413 full-text studies were reviewed, and data was extracted and charted from 66 studies that fulfilled all eligibility criteria [ 15 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Admittedly, some studies do report differences based on presence or absence of intellectual disability [35], toleration of change [36], and verbal communication ability [37]. Other studies exploring heterogeneity have reported associations between neurophysiological responses and various other variables in ASD [32,33,[38][39][40][41], including other measurements of sensory processing, such as questionnaires [34,[42][43][44][45]. However, no published neurophysiological studies have attempted to separate autistic individuals into subgroups based neural markers of sensory processing.…”
Section: Neurophysiologymentioning
confidence: 99%